Attitude and deformation coupled estimation of flexible satellite using low-cost sensors - Ghani, Marzieh; Assadian, Nima; Varatharajoo, Renuganth (Elsevier, 2022)
Solar panel flexibility plays an important role in the attitude control of satellites. Therefore, traditionally the deformations of flexible solar panels are measured with a series of sensors along the panels itself. This paper presents a novel maiden attempt to simultaneously estimate the attitude and deformation of a flexible satellite using only 2 low-cost attitude sensors namely the sun sensor and magnetometer measurements. The flexible satellite is considered as a central rigid body with two attached flexible panels in order to derive the governing dynamic equations based on the Lagrange’s equation. Both Extended Kalman filter (EKF) and Unscented Kalman Filter (UKF) are employed for the purpose of simultaneous attitude and deformation estimations. By performing a comparison between EKF and UKF through a Monte-Carlo simulation, UKF shows less sensitivity during eclipse. However, its computational time is much more than that of EKF. The numerical results also demonstrate that including the flexibility model in the developed estimation equations enables the algorithm to successfully estimate the deformation at any solar panel location without the need for any conventional sensor that directly measures the strain and/or deformation.